DOSIS DAN WAKTU APLIKASI POC DAUN LAMTORO TERHADAP PERTUMBUHAN VEGETATIF CABAI HIJAU - Sri Winayanti Siregar; Siti Yuli Meilanda Sormin; Putri Lukmanasari; Agung Primatara Marwan; Noprizal (UIR Press, 2025)
Green chili (Capsicum annuum L.) is a high-value horticultural crop whose vegetative growth is strongly influenced by nutrient availability, particularly nitrogen. Liquid organic fertilizer (LOF) derived from lamtoro leaves has potential as an environmentally friendly alternative fertilizer. This study aimed to evaluate the effects of dosage and application timing of lamtoro leaf liquid organic fertilizer on the vegetative growth of green chili. The research was conducted from May to August 2024 in Padang Lawas Utara, North Sumatra, using a factorial randomized block design with two factors. The first factor was LOF dosage, consisting of four levels: no LOF (D0), 100 ml/polybag (D1), 150 ml/polybag (D2), and 200 ml/polybag (D3). The second factor was application timing, namely 7 days after planting (DAP) (W1), 14 DAP (W2), and 21 DAP (W3), with three replications. Observed parameters included plant height, number of leaves, and stem diameter. Data were analyzed using ANOVA followed by the Least Significant Difference (LSD) test at the 5% level. The results showed that LOF dosage significantly affected all vegetative growth parameters of green chili. The highest plant height, number of leaves, and stem diameter were obtained at the dosage of 200 ml/polybag. Application timing at 14 and 21 DAP resulted in better vegetative growth than at 7 DAP. The combination of 200 ml/polybag LOF dosage with application timing at 14 and 21 DAP was the most effective treatment for improving vegetative growth of green chili.